Evaluation of Direct Cost of Adverse Drug Reactions to Highly Active Antiretroviral Therapy in Indian Human Immunodeficiency Virus Positive Patients - Rajesh, Radhakrishnan; Vidyasagar, Sudha; Muralidhar Varma, Danturulu; , Noorunnisa; Guddattu, Vasudeva (Journal of Clinical Research In HIV AIDS And Prevention, 2012)
In India, interruptions to highly active antiretroviral therapy (HAART) are due to adverse drug reactions (ADRs) and no reports on the direct cost incurred in the management of ADRs to HAART are available. There is a need to study direct cost incurred with ADRs to HAART to explore the high economic cost burden imposed by ADRs to HAART in HIV/AIDS patients. This study was aimed to evaluate the direct cost incurred in the management of ADRs to HAART in Indian HIV positive patients. This prospective study was conducted at a Medicine department in a South Indian tertiary care teaching hospitals were ADRs reporting system exist. HIV-positive hospitalized in-patients were identified and intensively monitored for ADRs to HAART. The World Health Organization (WHO) probability scale was used for causality assessment of ADRs. Modified Hart wig and Siegel scale was used for severity assessment of ADRs.Pearson chi-square test identified association of mean direct cost between ADRs and without ADRs by investigating total mean direct cost. The overall direct cost per ADRs to HAART was found to be higher in the context of expenditure on health care cost in India.
Keywords: Human immunodeficiency virus; direct cost; hospitalized patients; adverse drug reaction; highly active antiretroviral therapy.